2007
DOI: 10.1002/ca.20517
|View full text |Cite
|
Sign up to set email alerts
|

Superficial palmar communications between the ulnar and median nerves in Turkish cadavers

Abstract: The superficial palmar communicating branch between the ulnar and median nerves, the ramus communicans (RC), has been investigated by anatomical dissections in 30 hands of 15 cadavers in the Turkish population. A communicating branch between the ulnar and median nerves was found in 18 hands (60%). It was classified into 4 types: Type 1-RC emerging from the ulnar 4th common digital nerve (CDN) and uniting with the median 3rd CDN, Type 2-RC emerging from the median 3rd CDN and uniting with the ulnar 4th CDN, Typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 5 publications
1
28
0
2
Order By: Relevance
“…Prevalence may increase during the developmental period of the nervous system in the examined fetuses. Of the published studies listed in Table 3, Tagil et al (2007) reported data from Turkish cadavers that were closest to the present data; therefore, race may play a meaningful role in the results. No meaningful differences in the prevalence of CBs were noted between male and female and/or right and left hands.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…Prevalence may increase during the developmental period of the nervous system in the examined fetuses. Of the published studies listed in Table 3, Tagil et al (2007) reported data from Turkish cadavers that were closest to the present data; therefore, race may play a meaningful role in the results. No meaningful differences in the prevalence of CBs were noted between male and female and/or right and left hands.…”
Section: Discussionmentioning
confidence: 41%
“…Meals and Shaner (1983) classified the CBs as previously mentioned. Other studies defined a new variation in branch structures (Kawashima et al, 2004;Loukas et al, 2007;Tagil et al, 2007). In another study of 200 dissected palms of human adult cadavers, Loukas et al (2007) were able to identify a CB between the MNs and UNs in 85% of the specimens.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Se matiza que los trabajos de Beheiry (2004) Las conexiones NMC-NM deben considerarse en el examen clínico de lesiones nerviosas de axila y brazo así como para el abordaje quirúrgico en estas regiones; las lesiones de NMC o del NM ubicadas en sitios proximales o distales a los ramos comunicantes determinan modificaciones benéficas o catastróficas según el caso, del patrón biomecánico del miembro superior (Loukas & Aqueelah; Badawoud). El ramo comunicante de trayectoria oblicua entre el cuarto y tercer nervio digital común, observado en nuestro caso, es el más frecuentemente descrito en la literatura (Don Griot et al;Meals & Shaner;Ferrari & Gilbert;Tagil et al, 2007;Bas & Kleinert ) con rango del 60-80%.…”
Section: Discussionunclassified
“…To the Editor, Clinical Anatomy: Tagil et al (2007) have presented a paper on the superficial palmar communications between the ulnar and median nerves in Turkish cadavers.…”
mentioning
confidence: 97%